Do subjective norms matter in organic food buying intentions in Pakistan? - Mohd Shariff, Mohd Noor; Hafeez, Muhammad Haroon; Al-Swidi, Abdullah Kaid; Rafiul Huque, Sheikh Mohammed (2014)
The paper investigates the applicability of theory of planned behavior (TPB) with special emphasis on measuring the direct and moderating effects of subjective norms 012 attitude, perceived behavioral control and buying intention in context of buying organic food.Structured questionnaires were randomly distributed among academic staffs and students of two universities in Southern Punjab, Pakistan.Structural Equation Modeling was employed to test the proposed model fit. Results of the study showed that subjective norms significantly moderate the relationship between attitudes and buying intention as well as between perceived behavior control and buying intention. Furthermore, subjective norms significantly influence attitude towards buying intention.The paper provides useful insights for the academics and marketers:Academics may further explore the role of subjective norms in order to have a better understanding of their effects on component of TPB.Whereas, marketers can target the opinion leaders and reference groups to increase the demand of organic food.